The Premedical Student: His Identity: Characteristics of a Cohort of Premedical Students at the University of British Columbia - Anderson, Donald O. (1964)
A prospective study is currently being conducted of students who were freshmen at the University of British Columbia in 1961-1962. Three cohorts are being followed: 136 premedical students, 107 science students, and 136 persons comprising a sample of general arts students. At registration in 1961, the only demographic difference was that the Premedical cohort had a greater proportion of catholics and persons from upper occupational classes. Premedical students generally performed as well in high school as science students and better than general arts students, though the academic potential of science students as measured by achievement and aptitude tests was superior. Premedical students performed better on freshman examinations than the other cohorts, though a significantly larger proportion of science students (84.4%) actually passed into second year than of premedical students (75.0%). A disturbing observation was that by second year the Science cohort had recruited more than enough students to balance its losses, while the Premedical cohort had lost three times as many students as it recruited. The net effect was not much reduced by students who entered directly from senior matriculation or other universities, since these students were about twice as likely to enter the Science cohort as they were to enter the Premedical cohort.